MODEL BISNIS OLAHAN SINGKONG PADA USAHA PEUYEUM ABBAS SAWARGI KECAMATAN CIMENYAN KABUPATEN BANDUNG - Dewi Rengganis; Gema Wibawa Mukti; Yosini Deliana; Dhany Esperanza (Universitas Galuh Ciamis, 2018)
Commodities of food crops that have an important role for Indonesian people except rice is cassava. Cassava can be utilized into a variety of processed products and become one of the profitable business opportunities. Abbas Sawargi is the largest business in Bandung area that process cassava into peuyeum. Peuyeum is a food product of cassava fermentation with yeast and it is one of traditional food from West Java. This study aims to determine the business model on business Peuyeum Abbas Sawargi. This research is used qualitative design with case study technique. The primary data were obtained from the owner and manager of Peuyeum Abbass Sawargi. Data analysis using Business Model Canvas. The description of business model is obtained through business design process with storytelling technique, visual thinking, and prototyping. The result of the research shows that there is a building block which is the main thing in the formation of Peuyeum Abbas Sawargi business is by looking at Key Resources that already exist, such as using cassava that has been planted so that it can be used as business opportunity. There are several obstacles in business of Peueyum Abbas Sawargi on Key Activity block especially in the promotion, marketing and administration.Keywords : Processed Cassava, Peuyeum, Business Model Canvas.